Antioxidant and antibacterial potential of cinnamon bark, fennel seeds and peppermint leaves - Riaz, Muhammad; Murtaza, Mian Anjum; Ashraf, Sonia; Hafiz, Iram (Progress in Nutrition, 2022)
Background and Aims: Spices are commonly used as food adjuncts in improving the flavor, piquancy and aroma due to the presence of nutritionally significant ingredients. Present study was conducted to investigate the in vitro antioxidant and anti-bacterial activities of ethanolic and aqueous extracts of selected spices i.e. cinnamon bark, fennel seeds and peppermint leaves. Methods: Antioxidant potential was explored by determining the total phenolic contents, total flavonoids contents, total antioxidant activities and DPPH free radical scavenging potential. Antibacterial activities of selected spices have been evaluated through disc diffusion assay against selected Gram positive and Gram negative bacterial strains. Results: Phytochemical analysis revealed the presence of flavonoids, phenolics, alkaloids, steroids, saponins, coumarins and tannins. Significantly higher total phenolic contents, total flavonoids contents and total antioxidant activities were found in studied spices extracts. The results also revealed that aqueous extracts of spices showed higher antioxidant and antibacterial activities as compared to ethanolic extracts of selected spices. The study results showed that cinnamon bark, fennel seed and peppermint leaves possess significant antibacterial activity against foodborne and disease causing pathogens. The best antimicrobial activity was observed against Salmonella typhi and zones of inhibition were greater to that of standard antibiotic used. Conclusion: The study findings suggest the use of spices and their extracts as natural medicines to control various bacterial diseases. Moreover, the commercial products (beverages) may be prepared from the spices extracts.